The effect of increased general education in vocational schools: Evidence from a Hungarian vocational school reform - Joris Ghysels; Zoltán Hermann; Iryna Rud; Melline Somers (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
This paper aims at the evaluation of the reform of vocational education introduced in 1998 in Hungary. The reform extended the duration of education by one year, and increased teaching time spent on non-vocational subjects. The reform affected two of the three tracks in upper-secondary education in Hungary, vocational secondary school and vocational school. We estimate the effect of the reform on educational attainment, employment and wages in a comparative interrupted time series (CITS) framework, using the academic track and secondary school drop-outs as control groups. The results suggest that the reform has had heterogeneous effects. First, we detect no effect for the vocational secondary track, while the reform has improved labour market outcomes of vocational school students. Second, in the vocational school group the reform has increased men's wages, while not affected their employment. For women we found a positive employment effect, while wages have increased only for the younger cohorts.
Keywords: J08; J01; D00; 330; vocational education; reform; employment; wages; skills